Challenges of digital transformation in higher education institutions: a brief discussion - Rodrigues, Luis Silva (2020)
Like many industries, Higher Education Institutions (HEIs) have been exploiting emerging technologies as a way to improve performance and adapt to the increasingly technology-driven society. Although digital transformation is most often associated with business organizations, it is also an important issue for HEIs and presents some challenges that must be considered when defining digital policies and strategies. In this paper, as a starting point for our research, a brief discussion on the main challenges of digital transformation in HEIs is presented.